Laminate
The laminate, composed of phenolic resin and aliphatic hydrocarbon substrates bonded with a specific adhesive, addresses the inefficiency of fuel filtration in existing laminated filter media by enhancing fuel affinity, thereby achieving superior filtration performance.
Patent Information
- Application Number
- JP2021554287
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-11-01
- Filing Date
- 2020-10-12
- Publication Date
- 2025-04-16
- Estimated Expiration
- 2040-10-12
AI Technical Summary
Existing laminated filter media have a suboptimal affinity with fuels, leading to inefficient fuel filtration.
A laminate is created using substrates with phenolic resin and aliphatic hydrocarbon, bonded with an adhesive containing a high percentage of butylene terephthalate units, which enhances the affinity with fuels.
The laminate exhibits excellent affinity with fuels, resulting in efficient fuel filtration and improved performance compared to conventional filter media.
Smart Images

Figure 0007663076000002 
Figure 0007663076000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminate. [Background technology]
[0002] 2. Description of the Related Art Conventionally, filter media which are laminates have been used to remove suspended matter such as particles contained in various liquids such as fuels and automobile engine oils (hereinafter referred to as fuels, etc.) to obtain clean liquids.
[0003] As filter media, for example, the following Patent Documents 1 and 2 are disclosed. Patent Document 1 discloses a filter medium containing a plurality of fibers with different fiber diameters. Patent Document 2 discloses a filter medium in which the maximum and average pore sizes of the upstream and downstream layers are controlled to fall within specific ranges, and the upstream layer has fibers that are crimped and have an irregular cross-sectional shape. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 6-126112 [Patent Document 2] Japanese Patent Application Publication No. 5-49825 Summary of the Invention [Problem to be solved by the invention]
[0005] There is room for improvement in the absorption rate of fuel and the like into the filter media described in the above patent documents (hereinafter referred to as affinity with fuel and the like). [Means for solving the problem]
[0006] As a result of extensive research, the inventors discovered that by using a base material containing a phenolic resin and a specified aliphatic hydrocarbon, a laminate having high affinity for fuels, etc. can be obtained, and thus completed the present invention. That is, the present invention includes the following inventions. [1] A laminate having a first substrate and a second substrate, the first substrate and the second substrate being bonded together via an adhesive, the first substrate and the second substrate comprising a phenolic resin and an aliphatic hydrocarbon (A) detected in a retention time range of 12.0 to 30.0 minutes under measurement condition 1 of pyrolysis-gas chromatography-mass spectrometry (PY-GC / MS) described below, the adhesive comprising 65 mol % or more of butylene terephthalate units and 5 mol % or more of butylene isophthalate units, the adhesive having an acid value of 100 eq / ton or less, a glass transition temperature of -10 to 60°C, and a specific gravity of 1.20 or more. Pyrolysis-Gas Chromatography Mass Spectrometry (PY-GC / MS) Measurement Conditions 1: In the PY section, hold at 200°C for 10 minutes, in the GC section, hold at 40°C for 2 minutes, and then heat to 300°C at a heating rate of 10°C / min. [2] The laminate according to the above [1], wherein the first and second substrates each have a phenolic resin decomposition product of 0.1 mass% or less as detected by pyrolysis-gas chromatography / mass spectrometry (PY-GC / MS) under measurement condition 2 described below. Pyrolysis-Gas Chromatography Mass Spectrometry (PY-GC / MS) Measurement Conditions 2: In the PY section, hold at 500°C for 1 minute, and in the GC section, hold at 40°C for 2 minutes, then heat to 300°C at a rate of 10°C / min. [3] The laminate according to the above [1] or [2], wherein the first and second base materials each contain 0.1 mass % or more of the aliphatic hydrocarbon (A). [4] The laminate according to any one of the above [1] to [3], wherein the aliphatic hydrocarbon (A) contains a branched aliphatic hydrocarbon. [5] The laminate according to any one of the above [1] to [4], wherein the first and second base materials each contain at least one selected from polyethylene terephthalate and cellulose. Effect of the Invention
[0007] The laminate of the present invention has excellent affinity with fuel, etc., and can therefore efficiently filter the fuel, etc. [Brief description of the drawings]
[0008] [Figure 1] FIG. 2 is a diagram showing a method for calculating a melting point and a glass transition temperature. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The laminate of the present invention is a laminate having a first substrate and a second substrate, and the first substrate and the second substrate are bonded to each other via an adhesive.
[0010] <First substrate> The first substrate preferably contains at least one selected from polyethylene terephthalate and cellulose, and more preferably contains polyethylene terephthalate and cellulose.
[0011] The first substrate contains a phenolic resin and an aliphatic hydrocarbon (A) that is detected at a retention time of 12.0 to 30.0 minutes under the measurement condition 1 of pyrolysis-gas chromatography mass spectrometry (PY-GC / MS) described below. By using a substrate containing an aliphatic hydrocarbon (A), the laminate of the present invention becomes a laminate with excellent affinity with fuel, etc., and the fuel filterability is improved. The content of the aliphatic hydrocarbon (A) can be calculated under the measurement condition 1 of pyrolysis-gas chromatography mass spectrometry (PY-GC / MS) described below. This measurement is a method of quantifying based on the ratio of the peak area of the peak derived from the standard sample (dimethylsiloxane cyclic tetramer) in the obtained chromatogram to the peak area of the peak derived from the component to be quantified (aliphatic hydrocarbon under the measurement condition 1, and decomposition product of the phenolic resin under the measurement condition 2 described below). Specific measurement methods and measurement conditions other than those described below will be described later.
[0012] Pyrolysis-gas chromatography mass spectrometry (PY-GC / MS) measurement conditions 1: In the PY section, hold at 200°C for 10 minutes, and in the GC section, hold at 40°C for 2 minutes, and then heat to 300°C at a heating rate of 10°C / min.
[0013] The first base material preferably contains 0.1 mass % or more of aliphatic hydrocarbon (A), more preferably 0.5 mass % or more, and even more preferably 1 mass % or more, and the content of aliphatic hydrocarbon (A) is preferably 5 mass % or less, and more preferably 3 mass % or less. The aliphatic hydrocarbon (A) is preferably a branched aliphatic hydrocarbon, more preferably a branched aliphatic hydrocarbon having 6 to 50 carbon atoms, even more preferably a branched aliphatic hydrocarbon having 10 to 40 carbon atoms, and particularly preferably a branched aliphatic hydrocarbon having 15 to 30 carbon atoms.
[0014] The aliphatic hydrocarbon (A) contained in the first base material preferably contains two or more kinds of aliphatic hydrocarbons having different boiling points. Among them, it is preferable to contain a low-boiling aliphatic hydrocarbon (A1) having a retention time of 12.0 minutes or more and less than 19.1 minutes and a high-boiling aliphatic hydrocarbon (A2) having a retention time of 19.1 minutes or more and less than 30.0 minutes. By using a base material containing two or more kinds of aliphatic hydrocarbons having different boiling points, it is possible to further increase the affinity with fuels and the like. The first base material preferably contains 0.1 mass% or more of aliphatic hydrocarbon (A1) having a low boiling point, and more preferably contains 0.5 mass% or more. The content of the aliphatic hydrocarbon (A1) is preferably 3 mass% or less, and more preferably 1 mass% or less. In addition, the first base material preferably contains 0.1 mass% or more of aliphatic hydrocarbon (A2) having a high boiling point, and more preferably contains 0.5 mass% or more. The content of the aliphatic hydrocarbon (A2) is preferably 3 mass% or less, and more preferably 1 mass% or less.
[0015] The low-boiling aliphatic hydrocarbon (A1) is preferably an aliphatic hydrocarbon having 6 to 24 carbon atoms. Among them, a branched aliphatic hydrocarbon is more preferable, and a branched aliphatic hydrocarbon having 15 to 24 carbon atoms is even more preferable. Moreover, the high-boiling aliphatic hydrocarbon (A2) is preferably an aliphatic hydrocarbon having 25 to 50 carbon atoms. Among them, a branched aliphatic hydrocarbon is more preferable, and a branched aliphatic hydrocarbon having 25 to 35 carbon atoms is even more preferable.
[0016] The first substrate contains a phenolic resin, and the decomposition product of the phenolic resin detected under the measurement condition 2 of pyrolysis-gas chromatography mass spectrometry (PY-GC / MS) described below is preferably 0.5% by mass or less, more preferably 0.1% by mass or less. Heat resistance can be improved by using a substrate in which phenolic components are hardly precipitated even when heated to 500°C. Examples of the decomposition product of the phenolic resin detected under the measurement condition 2 described below include decomposition products such as o-cresol, p-cresol, 2,6-dimethylphenol, 2,4-dimethylphenol, trimethylphenol, and dihydroxydiphenylmethane, and the total amount of the decomposition products of the above six phenolic resins is defined as the decomposition product of the phenolic resin detected under the measurement condition 2 described below. Each compound is identified by MS fragments, and when the peaks of two or more compounds overlap, the compound is identified by the fragments and then the content is measured. Note that trimethylphenol and dihydroxydiphenylmethane include positional isomers.
[0017] Pyrolysis-gas chromatography mass spectrometry (PY-GC / MS) measurement conditions 2: In the PY section, hold at 500°C for 1 minute, and in the GC section, hold at 40°C for 2 minutes, then heat to 300°C at a heating rate of 10°C / min.
[0018] In the following, the decomposition product of the phenolic resin measured at the above-mentioned thermal decomposition temperature and thermal decomposition conditions will be simply referred to as "the decomposition product of the phenolic resin." Specific measurement methods and measurement conditions other than those described above will be described later.
[0019] The first substrate can be produced, for example, by making filter media fibers made of polyethylene terephthalate or cellulose into filter media base paper, impregnating this filter media base paper with a phenolic resin, and then curing the phenolic resin.
[0020] The composition of the first base material can be analyzed, for example, by the following method.
[0021] Approximately 100 mg of the first filter medium is collected and immersed in chloroform, and the extract is collected. After immersing in chloroform and then collecting the extract, the operation is repeated three times, and the residue is immersed in a mixture of chloroform and hexafluoro-2-propanol (chloroform:hexafluoro-2-propanol=50:50 (mass ratio)), and the extract is collected. After immersing in a mixture of chloroform and hexafluoro-2-propanol and then collecting the extract, the residue is subjected to IR analysis to identify the components. In addition, the six extracts obtained by the above operation are dried together, and then dissolved in a mixture of CDCl3 and trifluoroacetic acid (CDCl3:trifluoroacetic acid=85:15 (mass ratio)), and the residue is collected. 1 The components are identified by H NMR measurement. 1 The composition of the first filter medium can be identified from the results of the 1 H NMR measurement.
[0022] <Second substrate> The second substrate may be the same as the first substrate, or may be a different substrate, but it is preferable that the first substrate and the second substrate are the same. The preferred composition, physical properties, manufacturing method, etc. of the second substrate are the same as those of the first substrate, and therefore the description thereof will be omitted.
[0023] <Adhesive> The adhesive is mainly composed of a polyester resin, and specifically contains 65 mol % or more of butylene terephthalate units and 5 mol % or more of butylene isophthalate units.
[0024] The adhesive preferably contains 70 mol % or more of butylene terephthalate units, and more preferably contains 95 mol % or less of butylene terephthalate units, more preferably contains 90 mol % or less, more preferably contains 80 mol % or less, and even more preferably contains 75 mol % or less.
[0025] The adhesive contains butylene isophthalate units in an amount of preferably 10 mol % or more, more preferably 20 mol % or more, and even more preferably 25 mol % or more, and preferably 35 mol % or less, and more preferably 30 mol % or less.
[0026] The acid value of the adhesive is 100 eq / ton or less, preferably 10 to 70 eq / ton, and more preferably 15 to 60 eq / ton.
[0027] The glass transition temperature of the adhesive is -10 to 60°C, preferably 0 to 50°C, and more preferably 10 to 40°C.
[0028] The specific gravity of the adhesive is 1.20 or more, preferably 1.20 to 1.50, and more preferably 1.25 to 1.40.
[0029] The melting point of the adhesive is preferably 150 to 200°C, and more preferably 160 to 190°C.
[0030] The reduced viscosity of the adhesive is preferably 0.5 to 1.2 dl / g, and more preferably 0.6 to 1.0 dl / g.
[0031] The methods for measuring the acid value, glass transition temperature, specific gravity, melting point, and reduced viscosity of the adhesive will be described later.
[0032] The adhesive may contain units other than butylene terephthalate units and butylene isophthalate units (hereinafter referred to as other units). Specifically, the other units may be units derived from a diol component other than 1,4-butanediol, or may be units derived from a dicarboxylic acid other than terephthalic acid and isophthalic acid.
[0033] Examples of dicarboxylic acids constituting the other units include aromatic dicarboxylic acids such as orthophthalic acid, 1,5-naphthalic acid, 2,6-naphthalic acid, 4,4'-diphenyldicarboxylic acid, 2,2'-diphenyldicarboxylic acid, and 4,4'-diphenyletherdicarboxylic acid; and alicyclic dicarboxylic acids such as 1,4-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,2-cyclohexanedicarboxylic acid, and 4-methyl-1,2-cyclohexanedicarboxylic acid.
[0034] Examples of diol components constituting the other units include aliphatic diols such as ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,2-butanediol, 1,3-butanediol, 2-methyl-1,3-propanediol, 1,5-pentanediol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, neopentyl glycol, diethylene glycol, dipropylene glycol, 2,2,4-trimethyl-1,3-pentanediol, cyclohexanedimethanol, tricyclodecane dimethanol, and neopentyl glycol; alicyclic diols such as 1,4-cyclohexanedimethanol; and aromatic diols such as bisphenol A.
[0035] The content of other units in the adhesive is preferably 20 mol % or less, more preferably 10 mol % or less, even more preferably 5 mol % or less, particularly preferably 1 mol % or less, and most preferably 0 mol % (consisting only of butylene terephthalate units and butylene isophthalate units).
[0036] However, since units derived from aliphatic dicarboxylic acids impair hydrolysis resistance and reduce durability to high-temperature fuel, the adhesive preferably contains 3 mol % or less of units derived from aliphatic dicarboxylic acids, more preferably 1 mol % or less, and even more preferably 0 mol % (no units derived from aliphatic dicarboxylic acids).
[0037] The polyester used in the adhesive can be produced by a known method. For example, the above dicarboxylic acid and diol components can be esterified at 150 to 250° C., and then polycondensed at 230 to 300° C. under reduced pressure to obtain the desired polyester.
[0038] The adhesive may contain, as long as the effects of the present invention are not impaired, fillers such as talc, silica, mica, etc., plasticizers such as higher fatty acids, phenol-based, phosphorus-based, or amine-based antioxidants, sulfur-based heat aging inhibitors, titanium or phosphorus-based catalysts, or hydrolysis stabilizers such as epoxy or carbodiimide, etc. Even when a filler, plasticizer, antioxidant, hydrolysis stabilizer, etc. are contained, the content is preferably small, and specifically, the mass of the polyester resin in the adhesive is preferably 80 mass% or more, more preferably 90 mass% or more, even more preferably 95 mass% or more, particularly preferably 99 mass% or more, and most preferably 100 mass%.
[0039] The adhesive was dissolved in a mixture of CDCl3 and trifluoroacetic acid (CDCl3:trifluoroacetic acid=85:15 (mass ratio)) and the solution was centrifuged. 1 The components can be identified by H NMR measurement.
[0040] <Laminate> The laminate of the present invention is preferably used, for example, in a fuel filter for filtering fuel supplied to an internal combustion engine. This fuel filter can be installed in a passage for supplying fuel from a fuel pump to an internal combustion engine, or in a passage for returning fuel from the internal combustion engine to a fuel tank. The fuel filter may be installed either inside or outside the fuel tank. Furthermore, when the laminate of the present invention is housed in a filter housing to form a fuel filter, the filter housing can be integrated with a resin lid provided at the opening of the fuel tank.
[0041] The fuel filter may be, for example, a roll-shaped laminate in which the first substrate is a long flat filter material, the second substrate is a long corrugated filter material, and the long flat filter material and the long corrugated filter material are stacked and wound in the longitudinal direction.The fuel can be filtered by passing the fuel from one end to the other end in the width direction of the roll-shaped laminate.Hereinafter, one end of the width direction of the laminate may be referred to as the upstream side, and the other end may be referred to as the downstream side.
[0042] A method for producing a roll-shaped laminate will be described. A flat filter material can be produced by making filter material base paper from filter material fibers made of cellulose, impregnating this filter material base paper with a phenolic resin, and hardening it. A corrugated filter material can be obtained by forming a flat filter material into a wave shape using a corrugated roller. A long flat filter material and a long corrugated filter material are stacked, and an adhesive is applied between the flat filter material and the corrugated filter material on the downstream side of the laminate, and the laminate is pressed with a roller to heat and press the laminate. An adhesive is also applied between the flat filter material and the corrugated filter material on the upstream side so that the valley part of the corrugated filter material is fixed to the flat filter material. Next, the corrugated filter material side is wound so that the corrugated filter material side is on the radial inside to form a roll-shaped laminate. By applying an adhesive to the upstream side of the corrugated filter material during winding, the corrugated filter material and the flat filter material located on the radial inside are bonded to each other.
[0043] The fuel that flows in from the upstream side passes through the flat or corrugated filter material and flows downstream. The fuel is filtered as it passes through the flat or corrugated filter material.
[0044] This application claims the benefit of priority based on Japanese Patent Application No. 2019-199972, filed on November 1, 2019. The entire contents of the specification of Japanese Patent Application No. 2019-199972, filed on November 1, 2019, are incorporated by reference into this application. EXAMPLES
[0045] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to the following examples, and it is possible to carry out the present invention by making appropriate modifications within the scope of the above and below-mentioned aims, and all of these modifications are included in the technical scope of the present invention.
[0046] The methods for measuring the acid value, melting point, glass transition temperature, specific gravity, and reduced viscosity of the adhesive are described below.
[0047] <Acid value> 0.2g of sample resin (adhesive) was precisely weighed and dissolved in 20ml of chloroform. Then, it was titrated with 0.01N potassium hydroxide (ethanol solution) to obtain the acid value. Phenolphthalein solution was used as the indicator. The unit of acid value was eq / ton, that is, the equivalent weight per 1 ton of sample.
[0048] <Melting point / glass transition temperature> Using a differential scanning calorimeter "DSC220" manufactured by Seiko Denshi Kogyo Co., Ltd., 5 mg of sample resin (adhesive) was placed in an aluminum pan and the lid was pressed down to seal it. Next, after holding at 250°C for 5 minutes, it was rapidly cooled with liquid nitrogen, and then measured at a heating rate of 20°C / min from -100°C to 250°C. In the obtained curve, the intersection (circle in the figure) of the tangent (1) obtained from the baseline before the inflection point and the tangent (2) obtained from the baseline after the inflection point in the part where the inflection point appears in the DSC as shown in Figure 1 was taken as the glass transition temperature, and the minimum point of the endothermic peak (x in the figure) was taken as the melting point.
[0049] <Specific gravity> A measuring cylinder containing a calcium chloride solution with a known specific gravity was placed in a 30°C water bath for 15-20 minutes to warm it to the specified temperature. After that, a small piece (5mm x 5mm) of sample resin (adhesive) that had been crystallized at 60°C was placed in the measuring cylinder. The calcium chloride solution concentration was adjusted by adding water or a concentrated calcium chloride solution so that the sample floated in the liquid. A specific gravity meter was floated on the adjusted calcium chloride solution and measured.
[0050] <Reduced viscosity> Approximately 0.1 g of the sample resin (adhesive) was placed in a 25 ml measuring flask and dissolved in a mixed solvent (phenol / tetrachloroethane = 60 / 40 (weight ratio)), and the viscosity was measured at 30°C using an Ubbelohde viscosity tube.
[0051] <Pyrolysis-Gas Chromatography Mass Spectrometry> The aliphatic hydrocarbons in the filter were measured by the method described below in Measurement Method 1. Furthermore, the decomposition products of the phenolic resin in the filter were measured by the method described below in Measurement Method 2. Both Measurement Methods 1 and 2 were performed using a pyrolysis-gas chromatography mass spectrometry (PY-GC / MS) device.
[0052] (Measurement method 1) 0.5 mg of the sample was weighed and introduced into the PY section of a pyrolysis-gas chromatography mass spectrometry (PY-GC / MS) apparatus. 110 mg / L of dimethylsiloxane cyclic tetramer was used as the external standard substance, and measurements were performed using a single calibration method using the external standard method. The content of aliphatic hydrocarbons (A) was determined as the total amount of aliphatic hydrocarbons detected at retention times of 12.0 to 30.0 minutes.
[0053] (Measurement method 2) 0.2 mg of the sample was weighed and introduced into the PY section of a pyrolysis-gas chromatography mass spectrometry (PY-GC / MS) device. 110 mg / L of dimethylsiloxane cyclic tetramer was used as the external standard substance, and measurements were performed using a single calibration using the external standard method. The retention times (peak positions) of the decomposition products of the phenolic resins are as follows, and the total amount of the decomposition products of the following six phenolic resins was taken as the content of the decomposition products of the phenolic resins. o-Cresol 9.38 to 9.53 minutes p-Cresol 9.75 to 9.88 minutes 2,6-Dimethylphenol 10.28 to 10.42 minutes 2,4-Dimethylphenol 10.96 min to 11.15 min Trimethylphenol: 11.93 to 11.99 minutes Dihydroxydiphenylmethane 22.86 min - 23.07 min
[0054] The PY-GC / MS equipment and measurement conditions used in Measurement Methods 1 and 2 are as follows. Note that the measurement conditions for Measurement Methods 1 and 2 were the same except for the heating conditions of the cracking furnace. [PY Department] Equipment used: Double shot pyrolyzer PY-2020iD manufactured by Frontier Labs, Inc. Decomposition furnace heating conditions: 200℃×10min (when measuring aliphatic hydrocarbons: measurement condition 1), 500℃×1min (when measuring decomposition products of phenolic resins: measurement condition 2) Decomposition furnace heating atmosphere: Helium (He) Interface temperature: 320℃ [GC Department] ·Equipment used: Shimadzu Corporation GC / MS-QP2010Plus Column used: Ultra ALLOY-5 (MS / HT) manufactured by Frontier Labs, Inc. Length: 30 m, inner diameter: 0.25 mm, film thickness: 0.25 μm Column temperature: After 2 minutes at 40°C, increase the temperature at 10°C / min and hold at 300°C for 15 minutes. Carrier gas: Helium (He) Carrier gas control mode: constant pressure mode Column inlet pressure: 80kPa (column linear velocity during injection: 43.4cm / sec) Purge flow rate: 3.0mL / min ·Inlet temperature: 320℃ Injection method: Split injection method Split ratio: 30 [MS Department] Ion source temperature: 250℃ Interface temperature: 320℃ Measurement mode: SCAN mode Mass range (SCAN): m / z 30-550 Event duration: 0.5sec Ionization method: Electron Ionization Method (EI method) Ionization voltage: 70eV
[0055] <Filter A> The first substrate is a long flat filter material, the second substrate is a long corrugated filter material, and the long flat filter material and the long corrugated filter material are stacked together using an adhesive described below to prepare a roll-shaped filter A by winding it in the longitudinal direction. The method for preparing the roll-shaped filter A is as described in the above-mentioned <First substrate> and <Laminate>. The first substrate contains cellulose, phenolic resin, and polyethylene terephthalate, and the mass of polyethylene terephthalate contained in the substrate is 38% by mass. In addition, the first substrate contains 0.92% by mass of aliphatic hydrocarbons (A1) having a retention time of 12.0 minutes or more and less than 19.1 minutes under measurement condition 1 of pyrolysis-gas chromatography mass spectrometry (PY-GC / MS), 0.70% by mass of aliphatic hydrocarbons (A2) having a retention time of 19.1 minutes or more and 30.0 minutes or less, and the decomposition product of the phenolic resin under measurement condition 2 is 0.06% by mass. The second substrate was the same as the first substrate, and was obtained by forming the flat filter medium, which was the first substrate, into a corrugated shape using a corrugated roller. The adhesive contained 71 mol% butylene terephthalate units and 29 mol% butylene isophthalate units, and had an acid value of 37 eq / ton, a glass transition temperature of 27°C, a melting point of 176°C, a specific gravity of 1.30, and a reduced viscosity of 0.73 dl / g.
[0056] <Filter B> The first substrate is a long flat filter material, the second substrate is a long corrugated filter material, and the long flat filter material and the long corrugated filter material are stacked together using the adhesive described below to prepare a roll-shaped filter A by winding it in the longitudinal direction. The method for preparing the roll-shaped filter A is as described in the above-mentioned <Laminate> item. The first substrate contains cellulose, phenolic resin, and polyethylene terephthalate, and the mass of polyethylene terephthalate contained in the substrate is 50 mass%. In addition, the first substrate does not contain aliphatic hydrocarbons (A) having a retention time of 12.0 minutes or more and less than 30.0 minutes under measurement condition 1 of pyrolysis-gas chromatography / mass spectrometry (PY-GC / MS), and the decomposition product of the phenolic resin under measurement condition 2 is 0.13 mass%. The second substrate is the same as the first substrate, and is obtained by forming the flat filter material, which is the first substrate, into a corrugated shape using a corrugated roller. The adhesive contained 71 mol % butylene terephthalate units and 29 mol % butylene isophthalate units, and the adhesive had an acid value of 37 eq / ton, a glass transition temperature of 27°C, a melting point of 176°C, a specific gravity of 1.30, and a reduced viscosity of 0.73 dl / g.
[0057] <Measurement of mass change rate> Filter A with a thickness of 1.5 mm was cut into a size of 1 cm x 3.5 cm, and then left to stand for 12 hours at a constant temperature and humidity of 23 ° C and 55% RH, and the mass of the test piece of filter A was measured with a precision balance (about 0.21 g). Then, at room temperature of 23 ° C, one end (1 cm long surface) of the test piece of filter A was immersed in 10 ml of kerosene contained in a plastic container with an inner diameter of 6 cm φ, and the time until the kerosene permeated the other end was measured with a stopwatch. After the above test, the test piece of filter A was taken out and the kerosene on the surface was lightly wiped with a paper wiper, and the mass was measured with a precision balance, and the mass change rate (mass increase rate) from before the test was calculated using the following formula. Mass change rate (%) = 100 × (mass of filter after immersion in kerosene (g) - mass of filter before immersion in kerosene (g)) / mass of filter before immersion in kerosene (g)
[0058] The mass change rate was also calculated 15 minutes, 2 hours, 21 hours, and 24 hours after the end of the immersion.
[0059] The mass change rate of filter B was also measured in the same manner as above.
[0060] The mass change rates of filters A and B are summarized in Table 1 below.
[0061] [Table 1]
[0062] It was found that the time it took for kerosene to permeate from one end of the filter to the other was 11.00 seconds for Filter A, while it was 13.72 seconds for Filter B, which was shorter for Filter A. It was also found that the mass change rate (mass increase rate) immediately after the end of immersion was 152% for Filter A, while it was 100% for Filter B, meaning that Filter A had a greater mass change rate. From the above, it is clear that Filter A has a higher affinity for kerosene than Filter B, and absorbs kerosene in a shorter time.
[0063] In addition, the mass change rates 15 minutes, 2 hours, 21 hours, and 24 hours after the end of immersion showed that Filter A released the absorbed kerosene in a shorter time than Filter B. From the above, it was found that Filter A can filter kerosene with high efficiency.
Claims
1. A laminate having a first substrate and a second substrate, The first base material and the second base material are bonded to each other via an adhesive, The first and second base materials contain 0.5 to 3 mass % of a low-boiling aliphatic hydrocarbon (A1) having a retention time of 12.0 minutes or more and less than 19.1 minutes according to the following pyrolysis-gas chromatography / mass spectrometry (PY-GC / MS) measurement condition 1, and contain 0.5 to 3 mass % of a high-boiling aliphatic hydrocarbon (A2) having a retention time of 19.1 minutes or more and less than 30.0 minutes, the aliphatic hydrocarbon (A1) is a branched aliphatic hydrocarbon having 15 to 24 carbon atoms, and the aliphatic hydrocarbon (A2) is a branched aliphatic hydrocarbon having 25 to 35 carbon atoms, The first and second substrates are filter media made of polyethylene terephthalate, cellulose, and a phenolic resin; The adhesive contains 65 mol % or more of butylene terephthalate units and 5 mol % or more of butylene isophthalate units, and has an acid value of 100 eq / ton or less, a glass transition temperature of -10 to 60°C, and a specific gravity of 1.20 or more. A laminate comprising: Measurement conditions 1 for pyrolysis-gas chromatography-mass spectrometry (PY-GC / MS): [PY Department] ・Decomposition furnace heating conditions: 200°C x 10min Decomposition furnace heating atmosphere: Helium Interface temperature: 320°C [GC Department] Column used: Length 30 m, inner diameter 0.25 mm, film thickness 0.25 μm Column temperature: After 2 minutes at 40°C, increase the temperature at 10°C / min and hold at 300°C for 15 minutes. ・Carrier gas: Helium ・Carrier gas control mode: constant pressure mode Column inlet pressure: 80 kPa (column linear velocity during injection: 43.4 cm / sec) Purge flow rate: 3.0 mL / min ・Inlet temperature: 320℃ Injection method: Split injection method Split ratio: 30 [MS Department] Ion source temperature: 250° C. Interface temperature: 320°C Measurement mode: SCAN mode Measurement mass range (SCAN): m / z 30-550 Event time: 0.5 seconds Ionization method: Electron ionization method (EI method) Ionization voltage: 70 eV
2. The laminate according to claim 1, wherein the first and second base materials have a phenolic resin decomposition product of 0.1 mass% or less as detected by the following pyrolysis-gas chromatography / mass spectrometry (PY-GC / MS) measurement condition 2. Measurement conditions 2 for pyrolysis-gas chromatography / mass spectrometry (PY-GC / MS): [PY Department] ・Decomposition furnace heating conditions: 500°C x 1 min Decomposition furnace heating atmosphere: Helium Interface temperature: 320°C [GC Department] Column used: Length 30 m, inner diameter 0.25 mm, film thickness 0.25 μm Column temperature: After 2 minutes at 40°C, increase the temperature at 10°C / min and hold at 300°C for 15 minutes. ・Carrier gas: Helium ・Carrier gas control mode: constant pressure mode Column inlet pressure: 80 kPa (column linear velocity during injection: 43.4 cm / sec) Purge flow rate: 3.0 mL / min ・Inlet temperature: 320℃ Injection method: Split injection method Split ratio: 30 [MS Department] Ion source temperature: 250° C. Interface temperature: 320°C Measurement mode: SCAN mode Measurement mass range (SCAN): m / z 30-550 Event time: 0.5 seconds Ionization method: Electron ionization method (EI method) Ionization voltage: 70 eV
Citation Information
Patent Citations
Filtering material
JP1993049825A
Filter medium for filtration of liquid
JP1994126112A
Multilayer porous composite material
JP2015502833A
Cell separation filter, and production method of cell concentrate using the same
JP2016195589A
Filter media for removing water from a water-hydrocarbon emulsion having improved efficiency
JP2018525225A